Earthworms (Lumbricus terrestris L.) Mediate the Fertilizing Effect of Frass - Anne-Maïmiti Dulaurent; Guillaume Daoulas; Michel-Pierre Faucon; David Houben (Agronomy, 2020)
With the forecasted dramatic growth of insect rearing in the near future, frass (insect excreta) has been increasingly considered a sustainable resource for managing plant nutrition in cropping systems and a promising alternative to conventional fertilizer. However, the impact of soil fauna on its fertilizing effect has not been investigated so far. In this study, we investigated the effect of earthworms (Lumbricus terrestris L.) on nitrogen (N), phosphorus (P), potassium (K) and calcium (Ca) uptake and crop growth in the presence of frass from mealworm (Tenebrio molitor L.). Using a pot experiment, we found that earthworms increased N, P, K and Ca concentration in barley (Hordeum vulgare L.) in the presence of frass, suggesting that earthworm activity enhances the short-term recycling of nutrients from frass. Compared to treatments with and without frass and earthworms, the specific leaf area of barley was the highest in the presence of both earthworms and frass. This confirms that earthworms and frass have a synergistic effect on soil fertility. Overall, our study shows that earthworms may improve the efficiency of organic fertilizers and argues therefore for the importance of developing sustainable agricultural practices that promote earthworm populations.